The Effect of Increasing Rehabilitation Program Using Electric Stimulation On Rehabilitating Knee Joint Working Muscles Due to ACL Tear In Athletes - Hameed, Fatimah; Jawad, Mohammed (Journal of Physical Education, 2020)
The research aimed at designing a rehabilitation program using electric stimulation for rehabilitating knee joint working muscles as a result of ACL tear using an apparatus developed by the researchers that stimulate the muscle vibration and work as well as the ability to rehabilitate the join in shorter periods. In addition to that, it aimed at identifying the effect of this program on rehabilitating the knee joint working muscles. The researchers used the experimental method on Baghdad clubs’ players who suffer from complete knee joint ACL tear aged (19 – 24) years old. The results showed that the training program developed the working muscles significantly achieving normal levels of activity.